The Crustacean Hyperglycemic Hormone Superfamily: Progress Made in the Past Decade - Chen, Hsiang-Yin; Toullec, Jean-Yves; Lee, Chi-Ying (Frontiers in Endocrinology, 2020)
Earlier studies recognizing the importance of the decapod eyestalk in terms of endocrine regulation of crustacean physiology − molting, metabolism, reproduction, osmotic balance etc. − helped found the field of crustacean endocrinology. Characterization of the putative factors in the eyestalk using distinct functional bioassay ultimately led to the discovery of a group of structurally related and functionally diverse neuropeptides, crustacean hyperglycemic hormone (CHH), molt-inhibiting hormone (MIH), gonad-inhibiting hormone (GIH) or vitellogenesis-inhibiting hormone (VIH), and mandibular organ-inhibiting hormone (MOIH). These peptides, along with the first insect member (ion transport peptide, ITP), constitute the original arthropod members of the crustacean hyperglycemic hormone (CHH) superfamily. Presence of the genes encoding the CHH-superfamily peptides across representative ecdysozoan taxa has been established. The objective of this review is to, aside from providing a general framework, highlight the progresses obtained during the past decade or so. These progresses include, at least, continuous identification of the CHH-superfamily peptides, in particular in non-crustaceans, which reshaped the phylogenetic profile of the superfamily. Some of the new member peptides were characterized with novel function, providing exceptional opportunities for the understanding of structure-function relationship of the superfamily peptides. Functional studies are challenging, especially for those of crustacean and insect species, where the member peptides are widely expressed in various tissues and usually pleiotropic. Progresses have been made regarding CHH, ITP, and their alternatively spliced counterparts (CHH-L, ITP-L) in the regulation of metabolism and ionic/osmotic hemostasis under (eco)physiological, developmental, or pathological contexts, and MIH in stimulation of ovarian maturation, that implicates MIH as a regulator for coordinating the growth (molt) and reproduction. In addition, experimental elucidation of the steric structure and structure-function relationship gave better understandings of the structural basis of the functional diversification or overlapping among the member peptides. Finally, an important progress was made with the first-ever identification of the receptors for any of the superfamily peptides, specifically the receptors for ITPs of the silkworm, which would undoubtedly give great impetus to the functional study of the superfamily peptides for the years to come. Studies regarding these progresses are presented and synthesized, and prospective developments remarked.